Contemporary Danmei Fiction and Its Similitudes with Classical and Yanqing Literature - Aiqing Wang (Badan Pengembangan dan Pembinaan Bahasa, 2021)
Danmei, aka Boys Love, is a salient transgressive genre of Chinese Internet literature. Since entering China’s niche market in 1990s, the danmei subculture, predominantly in the form of original fictional creation, has established an enormous fanbase and demonstrated significance via thought-provoking works and social functions. Nonetheless, the danmei genre is not an innovation in the digital age, in that its bipartite dichotomy between seme ‘top’ and uke ‘bottom’ roles bears similarities to the dyad in caizi-jiaren ‘scholar-beauty’ anecdotes featuring masculine and feminine ideals in literary representations of heterosexual love and courtship, which can be attested in the 17th century and earlier extant accounts. Furthermore, the feminisation of danmei characters is analogous to an androgynous ideal in late-imperial narratives concerning heterosexual relationships during late Ming and early Qing dynasties, and the depiction of semes being masculine while ukes being feminine is consistent with the orthodox, indigenous Chinese masculinity which is comprised of wen ‘cultural attainment’ epitomising feminine traits and wu ‘martial valour’ epitomising masculine traits. In terms of modern literature, danmei is parallel to the (online) genre yanqing ‘romance’ that is frequently characterised by ‘Mary Sue’ and cliché-ridden narration.